Adapting the Advocate Health Care Taxonomy of Chaplaincy for a Pediatric Hospital Context: A Pilot Study. Issue 2 (3rd April 2019) - Nash, Paul; Roberts, Emma; Nash, Sally; Darby, Kathryn; Parwaz, Aftab Ahmed
Abstract : There is increasing pressure to provide an evidence base for chaplaincy with children and young people. This is an underresearched area, and current evidence is often anecdotal. Advocate Health Care in Chicago (funded by the Templeton Foundation working in partnership with the Health Care Chaplaincy Network) developed a 100-item taxonomy that was the starting point for a wider international initiative in developing a taxonomy for use in health care chaplaincy. The team at Birmingham Children's Hospital is part of this wider project and have sought to adapt and develop the original taxonomy for use in a specialist pediatric hospital. The Advocate structure of intended effect (why chaplains do what they do), method (what they do), and intervention (how they do it) was adapted by adding items generated from the chaplaincy team's research, writing, and experience. A total of 80 taxonomy charts were collected from 12 chaplaincy team members representing three world faiths. Quantitative data from the chart were analyzed and summarized. The findings were subsequently reviewed by the research team and a revised version of the taxonomy was produced based on the frequency of use of the additional items.